2020
DOI: 10.3390/microorganisms8060870
|View full text |Cite
|
Sign up to set email alerts
|

YycH and YycI Regulate Expression of Staphylococcus aureus Autolysins by Activation of WalRK Phosphorylation

Abstract: Staphylococcus aureus is a facultative pathogen that can encode numerous antibiotic resistance and immune evasion genes and can cause severe infections. Reduced susceptibility to last resort antibiotics such as vancomycin and daptomycin is often associated with mutations in walRK, an essential two-component regulatory system (TCS). This study focuses on the WalK accessory membrane proteins YycH and YycI and their influence on WalRK phosphorylation. Depletion of YycH and YycI by antisense RNA caused an impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…It encodes a member of the two-component regulatory system WalRK. In S. aureus, WalRK positively controls biofilm formation [51] and is essential for cell viability mainly by controlling the transcription of cell wall lysing enzymes [52]. WalKR in S. aureus activated the transcription of nine genes involved in the different steps of cell wall turnover (lytM, atlA, isaA, sceD, ssaA, and four ssaA-related genes) [51].…”
Section: Slow Cellular Process In the Mature Biofilmmentioning
confidence: 99%
“…It encodes a member of the two-component regulatory system WalRK. In S. aureus, WalRK positively controls biofilm formation [51] and is essential for cell viability mainly by controlling the transcription of cell wall lysing enzymes [52]. WalKR in S. aureus activated the transcription of nine genes involved in the different steps of cell wall turnover (lytM, atlA, isaA, sceD, ssaA, and four ssaA-related genes) [51].…”
Section: Slow Cellular Process In the Mature Biofilmmentioning
confidence: 99%
“…QTL Q25261 is located at gene SAOUHSC_00020 ( walR or yycG ) encoding cell envelope biogenesis 65 . walRK phosphorylation activates the expression of YycH and YycI to control cell wall metabolism and biofilm formation in S. aureus 66 , 67 .…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly appropriate when agonist or antagonist interactions occur within the membrane itself via the transmembrane regions of the kinase. A recent study employing this approach is that of Gajdiss et al (2020) who investigated the modulatory effects of two accessory membrane proteins, YycH and YycI, on the phosphorylation activities of the Staphylococcus aureus WalKR TCS [ 148 ].…”
Section: Identification and Characterisation Of Signalling Ligands And Inhibitors Using Full-length Shksmentioning
confidence: 99%
“…The presence of both accessory proteins together with WalK was required for high level expression of WalKR-expressed genes [ 158 ]. One of the aims of the recent study by Gajdiss et al (2020) of the S. aureus system was to obtain direct evidence for the roles of the YycH and YycI proteins in regulation of WalK activity [ 148 ]. Using purified full-length versions of all three membrane proteins reconstituted into phospholipid liposomes in various combinations, they showed that YycH and YycI stimulated WalK activity, confirming previous studies, and that both YycH and YycI proteins were necessary for full activation of the kinase in vitro, a finding also confirmed by accompanying in vivo studies [ 148 ].…”
Section: Identification and Characterisation Of Signalling Ligands And Inhibitors Using Full-length Shksmentioning
confidence: 99%
See 1 more Smart Citation